In Situ Protein Secondary Structure Determination in Ice: Raman Spectroscopy‐Based Process Analytical Tool for Frozen Storage of Biopharmaceuticals. Issue 8 (1st July 2014) - Roessl, Ulrich; Leitgeb, Stefan; Pieters, Sigrid; De Beer, Thomas; Nidetzky, Bernd
<x xml:space="preserve">Abstract</x> A Raman spectroscopy‐based method for in situ monitoring of secondary structural composition of proteins during frozen and thawed storage was developed. A set of reference proteins with different α‐helix and β‐sheet compositions was used for calibration and validation in a chemometric approach. Reference secondary structures were quantified with circular dichroism spectroscopy in the liquid state. Partial least squares regression models were established that enable estimation of secondary structure content from Raman spectra. Quantitative secondary structure determination in ice was accomplished for the first time and correlation with existing (qualitative) protein structural data from the frozen state was achieved. The method can be used in the presence of common stabilizing agents and is applicable in an industrial freezer setup. Raman spectroscopy represents a powerful, noninvasive, and flexibly applicable tool for protein stability monitoring during frozen storage. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2287–2295, 2014